Environment-friendly light flame-retardant heat-insulating aerogel coating and application thereof
By using an environmentally friendly, lightweight, flame-retardant, and heat-insulating aerogel coating formulation and a low-temperature curing process, the shortcomings of drone coatings in terms of lightweighting, weather resistance, and cost have been solved. This has achieved durability and heat insulation performance in high-temperature environments, making it suitable for extreme scenario protection of drones.
Patent Information
- Application Number
- CN202511198114.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-26
- Publication Date
- 2025-11-11
AI Technical Summary
Existing drone coatings are insufficient in terms of lightweighting, weather resistance, environmental friendliness, and cost, making it difficult to provide effective flame retardant and heat insulation protection in extreme environments.
The environmentally friendly, lightweight, flame-retardant, and heat-insulating aerogel coating formulation includes silica aerogel powder, ammonium polyphosphate, gelatin, hydroxyethyl cellulose, clay, and water-based epoxy resin. Through a low-temperature curing process, an aerogel-clay-gelatin cross-linked network is formed, generating an expanded carbon layer and a ceramic barrier, achieving high adhesion strength and heat insulation performance of the coating.
It achieves lightweight, low-cost coating with durability and flame-retardant heat insulation performance in high-temperature environments. The coating does not peel or crack at high temperatures, has ultra-low thermal conductivity and high bonding strength, and is suitable for the protection of drones in extreme scenarios.
Smart Images

Figure CN120924121A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of high-temperature protective materials technology, specifically relating to an environmentally friendly, lightweight, flame-retardant, and heat-insulating aerogel coating and its application. Background Technology
[0002] With the rapid development of drones in fields such as fire monitoring and high-temperature logistics, key components such as power battery compartments and engine shells face severe thermal management challenges: the core contradiction lies in the requirements for lightweighting and the need for resistance to ablation and thermal insulation in extreme thermal environments.
[0003] In the prior art, Chinese patent CN108997911A discloses a fire-retardant and heat-insulating coating that combines fire-retardant and heat-insulating properties through the synergistic effect of aerogel and ceramic powder. However, the addition of ceramic powder increases the weight, affecting the control of coating thickness and hindering lightweight application; its long-term weather resistance is also unclear. Chinese patent CN106700668A discloses a transparent aerogel coating that utilizes the low density of aerogel (0.06–0.12 g / cm³). 3 While achieving lightweight coatings, their durability in extreme environments is not addressed. Chinese patent CN108641431A discloses a drone coating for use in complex environments, which is resistant to acids, alkalis, and ultraviolet radiation, but the use of xylene solvent and lead white further increases costs and results in poor environmental performance. All of the aforementioned patents use complex formulations (such as coupling agents and multiple resins), and the processes involve high-speed dispersion or high-temperature modification, leading to high costs.
[0004] Furthermore, polymer-based coatings (such as epoxy resin) decompose violently and lose their flame retardancy above 200°C, and crack and peel off after 10 cycles of thermal cycling between 40°C and 120°C; aerogel felts, although possessing ultra-low thermal conductivity, have poor resistance to airflow erosion and cannot withstand rotor vibration; while ceramic coatings (such as zirconium oxide) have a density > 2.5 g / cm³. 3 This results in a 30% decrease in thrust-to-weight ratio, and plasma spraying is costly. A deeper technical bottleneck lies in process limitations; directly adding aerogel powder leads to weak interfacial bonding, and the coating's flame retardancy and mechanical strength—for example, the compressive strength of a coating with 22wt% hollow glass microspheres is only 0.5MPa—cannot simultaneously meet the engine vibration load. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention proposes an environmentally friendly, lightweight, flame-retardant, and heat-insulating aerogel coating and its applications. The aerogel coating has a simple formulation, low cost, and good rheological properties, facilitating coating application. It exhibits high adhesion between the aerogel coating and the substrate interface, and the coating does not peel or crack after repeated thermal cycling. The coating possesses ultra-low thermal conductivity, high bond strength, and extreme environment durability, achieving lightweight design, extreme environment durability, and low-cost manufacturing. This provides a breakthrough thermal protection solution for unmanned aerial vehicles (UAVs) in extreme scenarios such as petrochemical monitoring and forest fire rescue.
[0006] The objective of this invention is achieved through the following technical solution:
[0007] The first aspect of this invention discloses an environmentally friendly, lightweight, flame-retardant, and heat-insulating aerogel coating, comprising, by weight, 40-120 parts of raw material A and 80-150 parts of raw material B. Raw material A comprises 40-70 parts of water, 5-15 parts of silica aerogel powder, 1-5 parts of ammonium polyphosphate, and 10-40 parts of gelatin. Raw material B comprises 40-70 parts of water, 3-10 parts of hydroxyethyl cellulose, 20-50 parts of clay, 5-15 parts of tannic acid, and 5-20 parts of waterborne epoxy resin.
[0008] Furthermore, the clay is one or more of montmorillonite, sepiolite, and hydroxyapatite.
[0009] Furthermore, the silica aerogel is in the form of powder particles with a particle size ≤15μm, a porosity >90%, and a bulk density of 0.06~0.12g / cm³. 3 .
[0010] Furthermore, the preparation method of the environmentally friendly, lightweight, flame-retardant, and heat-insulating aerogel coating is as follows:
[0011] Step 1, Preparation of raw material A: First, add ammonium polyphosphate to water according to the stated mass proportions, dissolve it completely, then add silica aerogel powder and gelatin, stir evenly to obtain raw material A;
[0012] Step 2, Preparation of raw material B: First, add hydroxyethyl cellulose to water according to the stated mass fractions, dissolve it completely, then add clay, tannic acid and water-based epoxy resin, stir evenly to obtain raw material B;
[0013] Step 3: Mix raw material A and raw material B evenly according to the stated mass proportions to obtain an environmentally friendly, lightweight, flame-retardant, and heat-insulating aerogel coating.
[0014] Silica aerogel powder forms the thermal insulation framework of the coating. Its nanoporous structure is key to achieving ultra-low thermal conductivity, effectively inhibiting heat conduction through physical barriers. Ammonium polyphosphate, as a crucial flame retardant, decomposes at high temperatures to generate polyphosphoric acid and ammonia, catalyzing the dehydration and carbonization of tannic acid, gelatin, and other substances, and also promoting the expansion of the char layer through foaming gas. Gelatin functions as both a bio-based adhesive and a char-forming agent: during the curing stage, it forms a cross-linked network with tannic acid and epoxy resin, enhancing the coating's toughness; at high temperatures, it acts as a carbon source, participating in the formation of the expanded char layer. Hydroxyethyl cellulose acts as a thickener and suspender, preventing aerogel and clay sedimentation and ensuring uniform dispersion; clay, as a multifunctional reinforcing agent, forms a layered barrier within the char layer to block heat and gas, supports the framework to enhance mechanical strength, and promotes the formation of a ceramic barrier. Tannic acid is the core char-forming agent and crosslinking agent. During the curing stage, it crosslinks to enhance cohesion, and during the ablation stage, it mainly participates in the formation of an expanded char layer. Waterborne epoxy resin, as the main film-forming agent, provides coating adhesion and bulk strength, maintains structural stability at high temperatures, and residual carbon also participates in the formation of the char layer.
[0015] To ensure that the functions of each component are fully pre-dispersed and pre-protected before final mixing, and to ensure that they are uniformly distributed in the coating, a solid foundation is laid for the efficient and uniform formation of the expanded carbon layer and ceramic barrier during subsequent high-temperature ablation.
[0016] The separate formulation of raw materials A and B before mixing is primarily to prevent premature cross-linking of gelatin and tannic acid. Direct mixing of these two materials would immediately cause a reaction, forming insoluble gel clumps. This would result in the aerogel, clay, and other key functional particles being encapsulated and unevenly dispersed, leading to abnormally high system viscosity, making application difficult. Furthermore, the charring agent and catalyst would be isolated, preventing effective reaction at high temperatures, resulting in the inability to form or uneven distribution of the char layer, ultimately causing a sharp decline in thermal insulation and flame retardant properties. In addition, stepwise formulation ensures the independent and sufficient dispersion of each component: in raw material A, ammonium polyphosphate is dissolved first before adding aerogel and gelatin, using gelatin to prevent aerogel agglomeration; in raw material B, hydroxyethyl cellulose is dissolved first to provide a suspension environment, followed by the sequential addition of clay, tannic acid, and resin, ensuring thorough wetting and dispersion of each solid particle. By optimizing the dispersion state separately before gentle mixing, the independence and reactivity of each functional particle are maintained to the greatest extent, laying the foundation for the formation of a uniform and dense expanded char layer and ceramic barrier at high temperatures.
[0017] The second aspect of this invention discloses the application of the aforementioned environmentally friendly, lightweight, flame-retardant, and heat-insulating aerogel coating in the preparation of flame-retardant and heat-insulating aerogel coatings for unmanned aerial vehicles.
[0018] Furthermore, the application method is as follows: after cleaning the dirt on the surface of the drone substrate, spray a layer of corundum sand with a thickness of 25-35μm on the surface, then spray the coating onto the substrate, place it in an oven for curing treatment, and after curing, a flame-retardant and heat-insulating aerogel coating is obtained.
[0019] Furthermore, the thickness of the aerogel coating is 70±5μm.
[0020] Furthermore, the curing is carried out in an air atmosphere, with the temperature increased to 55-65°C at a heating rate of 2-5°C / min, and the curing time is 1-3 hours.
[0021] The third aspect of this invention discloses the application of the aforementioned environmentally friendly, lightweight, flame-retardant, and heat-insulating aerogel coating in the preparation of thermal insulation materials.
[0022] The environmentally friendly, lightweight, flame-retardant, and heat-insulating aerogel coating of this invention is sprayed onto the surface of a drone substrate. After curing, it forms a nano-interpenetrating three-dimensional porous framework composed of silica aerogel, clay, and gelatin. This reduces the thermal conductivity through physical barrier effects. The dynamic cross-linked network of tannic acid, gelatin, and water-based epoxy resin after curing enhances the coating's toughness and interfacial adhesion, creating a lightweight and durable coating. Especially under high-temperature environments, ammonium polyphosphate reacts with tannic acid and gelatin to form an expanded carbon layer, while clay forms a layered barrier. The expanded carbon layer, layered barrier, and aerogel nanopores together form a gradient heat insulation system, delaying heat transfer and heat release, further enhancing the stability of the three-dimensional framework at high temperatures, and improving heat insulation capabilities. When the coating encounters open flames or ultra-high-temperature environments, the tannic acid-gelatin-clay system undergoes an in-situ ceramization reaction catalyzed by ammonium polyphosphate, generating a dense carbon-ceramic composite protective barrier on the surface. This achieves synergistic protection from physical heat insulation to chemical flame retardancy, significantly improving the drone's survivability in extreme scenarios such as deflagration and sustained high temperatures.
[0023] The advantages and beneficial effects of this invention are:
[0024] 1. The aerogel coating of the present invention has a simple formulation, low cost, good rheological properties, and is easy to apply. The aerogel coating has high adhesion to the substrate interface and does not peel off or crack after repeated thermal cycling.
[0025] 2. The coating prepared by the aerogel coating of the present invention has excellent flame retardant and heat insulation properties, ultra-low thermal conductivity, high bonding strength and extreme environment durability. When preparing the aerogel coating, only a spraying thickness of 65-75μm is required, and the thermal conductivity of the coating is 0.020-0.025W / (m·K), which can simultaneously meet the requirements of UAVs for lightweighting and heat insulation.
[0026] 3. The present invention employs a low-temperature curing process in the preparation of the coating, which causes cross-linking within the coating, further enhancing its thermal insulation performance and significantly reducing its thermal conductivity. Attached Figure Description
[0027] Figure 1 The image shows the SEM pattern of the coating obtained in Example 1 of this invention.
[0028] Figure 2 The image shows the SEM pattern of the coating obtained in Comparative Example 1 of this invention.
[0029] Figure 3 The tensile curves are those of the coatings obtained in Examples 1-3 and Comparative Examples 1-4 of this invention.
[0030] Figure 4 The changes in the coating prepared in Example 1 of the present invention before and after being ablated by a butane spray gun for 30 seconds;
[0031] Figure 5 The microstructure of the coating obtained in Example 1 of this invention after being ablated by a butane spray gun for 30 seconds;
[0032] Figure 6 The image shows the macroscopic morphology of the coating prepared in Comparative Example 1 of this invention after being ablated by a butane spray gun for 30 seconds. Detailed Implementation
[0033] The present invention will be further described in detail below through specific embodiments. The following embodiments are merely descriptive and not limiting, and should not be used to limit the scope of protection of the present invention.
[0034] Example 1
[0035] A method for preparing an environmentally friendly, lightweight, flame-retardant, and heat-insulating aerogel coating, comprising the following steps:
[0036] Step 1, Preparation of Raw Material A: Weigh 40 parts by mass of deionized water and add it to a beaker. Turn on the stirrer and set the stirring speed to 200 r / min. First, add 1 part by mass of ammonium polyphosphate and dissolve it completely. Then, slowly add 5 parts by mass of silica aerogel powder and 10 parts by mass of gelatin. Continue stirring for 30 minutes until all raw materials are fully mixed and homogeneous to obtain Raw Material A.
[0037] Step 2, Preparation of raw material B: Take 40 parts by mass of deionized water and add it to another beaker. Stir at 200 r / min. First, add 3 parts by mass of analytical grade hydroxyethyl cellulose and dissolve it completely. Then add 20 parts by mass of montmorillonite, 5 parts by mass of tannic acid and 15 parts by mass of waterborne epoxy resin. Stir for 60 minutes to fully dissolve and mix the raw materials. Stir until uniform to obtain raw material B.
[0038] Step 3: Add 40 parts by weight of raw material A and 80 parts by weight of raw material B into a mixing container and stir at 300 r / min for 90 minutes to ensure that the two raw materials are fully mixed and homogeneous to obtain the aerogel coating.
[0039] Step 4: After cleaning the surface of the drone substrate, spray a 30±5μm layer of corundum sand onto the surface. Then, use a spray gun to evenly spray the prepared aerogel coating onto the substrate surface, controlling the spray thickness to 70±5μm. Next, place the sprayed substrate in an air-atmosphere oven and heat it to 60℃ at a rate of 5℃ / min for 2 hours for curing. After curing, allow it to cool naturally to room temperature to obtain the finished aerogel coating.
[0040] Example 2
[0041] A method for preparing an environmentally friendly, lightweight, flame-retardant, and heat-insulating aerogel coating, comprising the following steps:
[0042] Step 1, Preparation of raw material A: Weigh 70 parts by weight of deionized water and place it in a beaker. Set the stirring speed to 250 r / min. First, add 5 parts by weight of ammonium polyphosphate and dissolve it completely. Then, add 15 parts by weight of silica aerogel powder and 40 parts by weight of gelatin in sequence. Stir for 45 minutes to ensure that the raw materials are fully dispersed and uniform, thus obtaining raw material A.
[0043] Step 2, Preparation of raw material B: Add 70 parts by weight of deionized water to a beaker and stir at 250 r / min. First, add 10 parts by weight of hydroxyethyl cellulose and dissolve it completely. Then, add 50 parts by weight of clay mixed with sepiolite and hydroxyapatite in a 2:1 ratio, 15 parts by weight of tannic acid, and 20 parts by weight of waterborne epoxy resin. Stir continuously at 300 r / min for 90 minutes to obtain raw material B.
[0044] Step 3: Add 120 parts by weight of raw material A and 150 parts by weight of raw material B into a mixing container and stir at 350 r / min for 120 minutes to fully mix and obtain the aerogel thermal insulation coating.
[0045] Step 4: After cleaning the surface of the drone substrate, spray a 30±5μm layer of corundum sand onto the surface. Then, use a spray gun to evenly spray the aerogel coating onto the substrate surface, with a coating thickness of 70μm. Place the sprayed substrate in an air-atmosphere oven and heat it to 55℃ at a rate of 3℃ / min, curing for 2 hours. After curing, allow it to cool naturally to room temperature to obtain the finished aerogel coating.
[0046] Example 3
[0047] A method for preparing an environmentally friendly, lightweight, flame-retardant, and heat-insulating aerogel coating, comprising the following steps:
[0048] Step 1, Preparation of Raw Material A: Weigh 55 parts by weight of deionized water and add it to a beaker. Set the stirring speed to 220 r / min. First, add 3 parts by weight of ammonium polyphosphate and dissolve it completely. Then, slowly add 10 parts by weight of silica aerogel powder and 25 parts by weight of gelatin. Continue stirring for 40 minutes to ensure that all raw materials are thoroughly mixed and homogeneous, thus obtaining Raw Material A.
[0049] Step 2, Preparation of raw material B: Take 55 parts by weight of deionized water and place it in another beaker. Stir at 220 r / min. First, add 6 parts by weight of hydroxyethyl cellulose and dissolve it completely. Then, add 35 parts by weight of clay mixed with montmorillonite and sepiolite in a 1:1 ratio, 10 parts by weight of analytical grade tannic acid, and 10 parts by weight of waterborne epoxy resin. Stir for 75 minutes to ensure that all raw materials are fully dissolved and mixed to prepare raw material B.
[0050] Step 3: Add 80 parts by weight of raw material A and 115 parts by weight of raw material B into a mixing container and stir at 320 r / min for 105 minutes to fully blend the two raw materials and obtain the aerogel thermal insulation coating.
[0051] Step 4: After cleaning the surface of the drone substrate, spray a 30±5μm layer of corundum sand onto the surface. Then, use a spray gun to evenly spray the aerogel coating onto the substrate surface, with a coating thickness of 70μm. Place the sprayed substrate in an air-atmosphere oven and heat it to 65℃ at a heating rate of 4℃ / min for 2 hours to cure. After curing, allow it to cool naturally to room temperature to obtain the aerogel coating.
[0052] Comparative Example 1
[0053] The only difference from Example 1 is that no curing process is performed, and the coating is allowed to dry at room temperature.
[0054] Comparative Example 2
[0055] The only difference from Example 1 is that ammonium polyphosphate is replaced with melamine.
[0056] Comparative Example 3
[0057] The only difference from Example 1 is that gelatin is replaced with polyvinyl alcohol (PVA).
[0058] Comparative Example 4
[0059] The only difference from Example 1 is that the waterborne epoxy resin is replaced with a waterborne acrylic emulsion.
[0060] Performance and Testing
[0061] The coatings prepared in Example 1 and Comparative Example 1 were subjected to SEM analysis, as shown below. Figures 1-2 As shown in the figure, Figure 1The coating surface is dense and uniform, with no macroscopic defects. Figure 2 The uncured coating exhibits a loose, porous, and disordered stacked state, with severe agglomeration of aerogel particles and numerous microcracks and pores. The lack of curing results in the absence of a dynamic cross-linking network, preventing the aerogel particles from being encapsulated and hindering the construction of a stable aerogel-clay-gelatin three-dimensional framework, thus affecting interfacial adhesion and thermal insulation performance.
[0062] The coating samples prepared in Example 1 and Comparative Examples 1-4 were subjected to ablation under a butane torch (flame center temperature ≥1300℃), with the flame 10mm away from the coating surface. After ablation for 30 seconds, the samples were allowed to cool naturally to room temperature. The before-and-after changes are shown in the figure. Figure 4 As shown. It can be seen that before ablation ( Figure 4 (Left) The coating surface is smooth, grayish-white, and free of cracks. A macroscopic photograph of the coating after 30 seconds of ablation is shown below. Figure 4 As shown on the right, there is no cracking or peeling on the surface. SEM observation was performed on the coating of Example 1 after 30 seconds of ablation. Figure 5 The results showed that a uniformly distributed honeycomb-shaped ceramic layer was formed on the ablated surface. This ceramic layer was generated through an in-situ ceramicization reaction of tannic acid-gelatin-clay system catalyzed by ammonium polyphosphate. The ablated surface formed a dense carbon-ceramic composite protective barrier, achieving synergistic protection from physical heat insulation to chemical flame retardancy, significantly improving the survivability of UAVs in extreme scenarios such as deflagration and continuous high temperatures.
[0063] Meanwhile, an ablation experiment was conducted on Comparative Example 1 ( Figure 6 Within 10 seconds, the coating bubbled, cracked, and peeled off. The lack of curing prevented the coating from forming a cross-linked network, causing the coating to disintegrate rapidly.
[0064] The tensile bond strength and thermal conductivity of the aerogel coatings prepared in the examples and comparative examples were tested, and their thermal conductivity and tensile bond strength are shown in Table 1.
[0065] Table 1 Tensile bond strength and thermal conductivity of environmentally friendly lightweight flame-retardant and heat-insulating aerogel coatings
[0066] Tensile bond strength (MPa) Thermal conductivity (W / (m·K)) Example 1 3.83 0.0020 Example 2 3.79 0.0025 Example 3 3.65 0.0023 Comparative Example 1 0.75 0.0040 Comparative Example 2 2.95 0.0042 Comparative Example 3 1.98 0.0045 Comparative Example 4 2.10 0.0039
[0067] Tensile tests were performed on the coatings obtained in Examples 1-3 and Comparative Examples 1-4, and the tensile curves are shown below. Figure 3As shown in Table 1, the coatings of this invention (Examples 1-3) exhibit high strength and high toughness, with tensile strengths ranging from 3.65 to 3.83 MPa, and a significant yield plateau is observed in the stress-strain curves. This performance is attributed to the fact that tannic acid, gelatin, and waterborne epoxy resin form a cross-linked network through dynamic intermolecular interactions. This dynamic relationship can undergo reversible dissociation and reconstruction under external forces, reducing stress concentration by dispersing and consuming energy, thereby giving the coating good ductility and deformation recovery capabilities. The cross-linked network, combined with the aerogel-clay-gelatin three-dimensional interpenetrating framework, synergistically supports the load and prevents the propagation of microcracks.
[0068] Comparative Example 2 replaced ammonium polyphosphate with melamine. The resulting coating exhibited decreased tensile bond strength and increased thermal conductivity. This is because the ammonium polyphosphate aqueous solution is weakly acidic, and this microenvironment promotes the cross-linking reaction between gelatin and tannic acid, thereby forming a more stable network structure in the early stages of curing and improving the coating's bond strength. Simultaneously, the acidic environment also helps stabilize the dispersion system. In contrast, the melamine aqueous solution is nearly neutral and cannot provide a similar acidic catalytic environment, making it difficult to promote effective cross-linking between gelatin and tannic acid. Consequently, the overall integrity and bond strength of the cured coating are significantly weaker than the system using ammonium polyphosphate.
[0069] In Comparative Example 3, replacing gelatin with polyvinyl alcohol (PVA) resulted in a coating with significantly reduced tensile bond strength and increased thermal conductivity. This is because the protein chain structure of gelatin facilitates specific interactions with aerogel particles and clay sheets, forming an interpenetrating network. PVA, with its different chain structure, cannot form the same effective three-dimensional interpenetrating structure, affecting the coating's integrity, strength, and thermal insulation. This leads to a more brittle and less flexible coating, and the resulting three-dimensional network structure is less dense and uniform than in Example 1, impacting both thermal insulation and mechanical properties.
[0070] In Comparative Example 4, replacing the waterborne epoxy resin with a waterborne acrylic emulsion resulted in a coating with decreased tensile bond strength and increased thermal conductivity. This is because the epoxy groups in the waterborne epoxy resin can undergo chemical cross-linking reactions with the active groups such as the amino groups of gelatin and the phenolic hydroxyl groups of tannic acid, forming a robust and stable three-dimensional network structure during the curing stage. In contrast, the waterborne acrylic emulsion mainly forms films through physical film formation and weak hydrogen bonding, lacking effective chemical cross-linking points, leading to a significant reduction in the initial cohesive strength and bond strength of the cured coating. Epoxy resins possess inherently high adhesion to various substrates, while acrylic resins typically have lower adhesion and modulus than epoxy resins, resulting in weakened adhesion between the coating and the substrate.
[0071] The thermal conductivity of the coating was tested using the transient hot wire method. Coating samples prepared in Examples 1-3 and Comparative Examples 1-4 were fabricated into specimens with uniform thickness and smooth surfaces, and placed in close contact between the sensors of a thermal conductivity meter (TC3000E, XIATECH, CHN). The measured thermal conductivity at room temperature is shown in Table 1. As can be seen from the data in Table 1, the coating described in this invention has a low thermal conductivity, while the thermal conductivity of the comparative samples is significantly higher. This is because the low-temperature curing process in these examples successfully constructed a nano-interpenetrating three-dimensional framework of aerogel-clay-gelatin, whose abundant nanopores effectively suppressed air convection and solid heat conduction; simultaneously, the cross-linked network formed by tannic acid-gelatin-waterborne epoxy resin further enhanced phonon scattering and reduced thermal vibration heat transfer. In contrast, Comparative Example 1, due to its lack of curing, failed to form a three-dimensional porous framework, resulting in numerous microscopic defects and thermal bridges, making heat conduction easier. Comparative Examples 2, 3, and 4, due to their formulation defects, resulted in insufficient density, poor integrity, or excessively low interfacial thermal resistance in the cured coating structure, thereby increasing the thermal conductivity.
[0072] A butane torch (flame center temperature ≥1300℃) was used to burn a fixed area at a distance of 20mm from the coating surface for 30 seconds, followed by immediate cooling to room temperature for 60 seconds. This process was recorded as one cycle. The number of cycles when the coating failed due to cracking, blistering, or peeling was recorded, and the results are shown in Table 2.
[0073] Table 2 Results of thermal shock cycle test of coating
[0074]
[0075] As shown in Table 2, the coatings described in this invention can withstand more than five rigorous flame thermal shock cycles while maintaining structural integrity. This is attributed to the excellent thermal stability of their aerogel-clay-gelatin three-dimensional interpenetrating framework and the toughness of the tannic acid-gelatin-epoxy resin crosslinking network, which together buffer the internal stress generated by rapid heating and cooling. Simultaneously, the polyphosphoric acid generated by the decomposition of ammonium polyphosphate at high temperatures strongly catalyzes the reaction of tannic acid, gelatin, and clay surface groups, forming a continuous protective barrier with a carbonized layer as the matrix and embedded ceramic sheets. This barrier not only effectively blocks heat transfer to the substrate, but its self-formed aerogel pore-expanded carbon layer-ceramic sheet thermal insulation structure significantly delays thermal shock and prevents the coating from peeling off and failing under high-temperature, high-speed airflow.
[0076] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several modifications and improvements can be made without departing from the inventive concept, and these all fall within the protection scope of the present invention.
Claims
1. An environmentally friendly, lightweight, flame-retardant, and heat-insulating aerogel coating, characterized in that, By weight, it includes 40-120 parts of raw material A and 80-150 parts of raw material B. Raw material A includes 40-70 parts of water, 5-15 parts of silica aerogel powder, 1-5 parts of ammonium polyphosphate, and 10-40 parts of gelatin. Raw material B includes 40-70 parts of water, 3-10 parts of hydroxyethyl cellulose, 20-50 parts of clay, 5-15 parts of tannic acid, and 5-20 parts of waterborne epoxy resin.
2. The environmentally friendly, lightweight, flame-retardant, and heat-insulating aerogel coating according to claim 1, characterized in that, The clay is one or more of montmorillonite, sepiolite, and hydroxyapatite.
3. The environmentally friendly, lightweight, flame-retardant, and heat-insulating aerogel coating according to claim 1, characterized in that, The silica aerogel is a powder particle with a particle size ≤15μm, a porosity >90%, and a bulk density of 0.06~0.12g / cm³. 3 .
4. The environmentally friendly, lightweight, flame-retardant, and heat-insulating aerogel coating according to claim 1, characterized in that, Its preparation method is as follows: Step 1, Preparation of raw material A: First, add ammonium polyphosphate to water according to the stated mass proportions, dissolve it completely, then add silica aerogel powder and gelatin, stir evenly to obtain raw material A; Step 2, Preparation of raw material B: First, add hydroxyethyl cellulose to water according to the stated mass fractions, dissolve it completely, then add clay, tannic acid and water-based epoxy resin, stir evenly to obtain raw material B; Step 3: Mix raw material A and raw material B evenly according to the stated mass proportions to obtain an environmentally friendly, lightweight, flame-retardant, and heat-insulating aerogel coating.
5. The application of the environmentally friendly lightweight flame-retardant and heat-insulating aerogel coating as described in any one of claims 1 to 4 in the preparation of flame-retardant and heat-insulating aerogel coatings for unmanned aerial vehicles.
6. The application according to claim 5, characterized in that, The application method is as follows: after cleaning the dirt on the surface of the drone substrate, spray a layer of 25-35μm corundum sand on the surface, then spray the coating onto the substrate, place it in an oven for curing treatment, and after curing, a flame-retardant and heat-insulating aerogel coating is obtained.
7. The application according to claim 6, characterized in that, The curing process is carried out in an air atmosphere, with the temperature increased to 55-65°C at a rate of 2-5°C / min, and the curing time is 1-3 hours.
8. The application according to claim 6, characterized in that, The thickness of the aerogel coating is 65–75 μm.
9. The application of the environmentally friendly, lightweight, flame-retardant, and heat-insulating aerogel coating as described in any one of claims 1 to 4 in the preparation of thermal insulation materials.
Citation Information
Patent Citations
Transparent aerogel heat-insulating coating and preparation method thereof
CN106700668A
Unmanned aerial vehicle paint applied in complicated environment
CN108641431A
Aerogel waterproof and heat-insulating coating as well as preparation method thereof
CN108997911A